Effect of Perfluorane on Electric Pulse-Modified Red Blood Cell Membranes - V. V. Moroz; Ye. K. Kozlova; M. S. Bogushevich; P. Yu. Alekseyeva; A. M. Chernysh (Общая реаниматология, 2005)
As a plasma substitute clinical medicine uses perfluorane that is an antishock, antiischemic, and cardioprotective agent having a function of transferring O2 and CO2. The authors have investigated the interaction of perfluorane particles with human erythrocytic membranes. The erythrocytic membranes were modified with an impulse electrical field in the experiment. The induced calibrated electroporation of the membranes permitted the detection of the masked effects of perfluorane on blood cells. A clinical defibrillator was used as a source of an impulse electrical field. An electrical impulse was applied to the titanium electrodes placed into the quartz cuvette containing a red blood suspension. Perfluorane was added at concentrations of 5—100 ^l/ml of the suspension. The results were assessed by the optical density of the suspension before and after the action of perfluorane and the impulse electrical field. More than 450 experiments were carried out in three series. The authors studied the effect of perfluorane at concentrations of 10—100 ^l/ml on the modified erythrocytic membranes in the first series, the combined effect of the agent and the second electrical impulse in the second series, and the effect of perfluorane at concentrations of 5, 25, and 100 ^l/ml on the membrane upon combined exposures to positive and negative impulse electrical field in the third series. The first and second series of experiments indicated the strengthening (decelerating the rate of hemolysis) effect of perfluorane administered at small concentrations and its damaging effect given at high concentrations. Exposure to electrical fields of different directions in the second and third series made it possible to change the shear vector of charged perfluorane particles against the blood cells and to reveal a number of composite nonlinear effects of their interaction. The paper discusses the possible mechanisms of interaction of perfluorane with erythrocytic membranes, which are associated with the structural, charge, and electrochemical asymmetry of the mem-brane-perfluorane system.